Evaluation of novel chromatographic prototypes for supercoiled plasmid DNA polishing - Ferreira, Pedro L.; Marie, Helena; Berger, Tim; Edelmann, Bianca; Rammo, Oliver; Sousa, Fani (Frontiers in Bioengineering and Biotechnology, 2024)
Since the world first approved gene therapeutics, nucleic acid-based therapies have gained prominence. Several strategies for DNA-based therapy have been approved, and numerous clinical trials for plasmid DNA (pDNA)-based vaccines are currently in development. Due to the rising interest in pDNA for vaccination and gene therapy, plasmid manufacturing must become more effective. One of the most critical steps is downstream processing, involving isolation and purification procedures. To comply with the regulatory guidelines, pDNA must be available as a highly purified, homogeneous preparation of supercoiled pDNA (sc pDNA). This process undertakes several challenges, primarily due to the diversity of molecules derived from the producer organism.In this study, different resins were tested for the adsorption and selective polishing of sc pDNA. To identify optimal pDNA adsorption conditions, batch and column assays were performed with different resins while promoting electrostatic and hydrophobic interactions. The effect of ionic strength, pH, and contact time were evaluated and optimized. Additionally, static and dynamic binding capacities were determined for the selected resins. Analytical chromatography and agarose gel electrophoresis were used to assess the selectivity of the most promising resins toward sc pDNA isoform. Also, genomic DNA, endotoxins, and proteins were quantified to characterize the final sc pDNA quality. At the same time, the recovery and purity yields were evaluated by quantification of sc pDNA after the purification procedure.Overall, the results of the chromatographic assays using agmatine-and arginine-based resins have shown promising potential for sc pDNA polishing. Both resins demonstrated excellent binding capacity for pDNA, with agmatine outperforming arginine-based resin in terms of capacity. However, arginine-based resin exhibited a superior pDNA recovery yield, reaching a notable 52.2% recovery compared to 10.09% from agmatine. Furthermore, both resins exhibited high relative purity levels above 90% for the sc pDNA. The comprehensive characterization of the recovered sc pDNA also revealed a significant reduction in gDNA levels, reinforcing the potential of these prototypes for obtaining high-quality and pure sc pDNA. These findings highlight the promising applications of both resins in scalable pDNA purification processes for gene therapy and biopharmaceutical applications.